Thermoresponsive poly(ϵ‐caprolactone)‐graft‐poly(N‐isopropylacrylamide) graft copolymers prepared by a combination of ring‐opening polymerization and sequential azide–alkyne click chemistry. Issue 3 (15th September 2014) - Li, Mingming; Pan, Pengju; Shan, Guorong; Bao, Yongzhong
<x xml:space="preserve">Abstract</x> A straightforward strategy is described to synthesize poly(ϵ‐caprolactone)‐graft‐poly(N‐isopropylacrylamide) (PCL‐g‐PNIPAAm) amphiphilic graft copolymers consisting of potentially biodegradable polyester backbone and thermoresponsive grafting chains via a combination of ring‐opening polymerization, atom transfer radical polymerization and azide–alkyne click chemistry. PCL‐g‐PNIPAAm graft copolymers self‐assemble into thermosensitive micelles in aqueous solution. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>